A new species of Palaemon (Crustacea, Decapoda, Palaemonidae) from West Africa, with a re-description of Palaemon maculatus (Thallwitz, 1892) - Ashelby, Christopher W.; de Grave, Sammy (Zootaxa, 2009)
A new species of Palaemon, P. powelli sp. nov., is described from tropical West Africa. The new species is characterised by the shape and proportions of its chelae, the shape of the rostrum, spacing between dorsal rostral teeth and a poorly developed grooming brush on the fifth pereiopod. Palaemon maculatus (Thallwitz, 1892) is redescribed and can be separated from other eastern Atlantic members of the genus by the form of the rostrum, the proportions of the segments of pereiopod 2 and the large number of rows of setae in the grooming brush on the fifth pereiopod.